Seni Kulinari, Kekuasaan, dan Multikulturalisme dalam Master Cooking Boy/ The Real Master Cooking Boy Karya Etsushi Ogawa - Kurnia, Lilawati (Wacana, Journal of the Humanities of Indonesia, 2006)
This essay examines manga, the japanese comic Master Cooking Boy" and inquires what the manga offers to the reader beside being a popular reading. This essay reviews the history of manga and its function in the Japanese culture. The paper unravels the theories of cultural studies such as hegemony and multiculturalism in the analyse of this manga. This paper discusses the wider horizon of manga as a field of hegemony discourse and multiculturalism. It opens the possibilities to analyse manga in a different perspective and shows how ideology can operates in the popular literature.